Role of Digital Ethics Frameworks in Shaping Corporate Governance Policies in Emerging Tech Startups in Indonesia - Sudirwo Sudirwo; Suprihono Setyawan; Valida Togrul Garayeva (Management Dynamics: International Journal of Management and Digital Sciences, 2024)
Digital ethics frameworks play a crucial role in shaping corporate governance in tech startups, ensuring transparency, accountability, and trust within organizations. As digital technologies continue to evolve and become more integrated into daily operations, startups face both opportunities and challenges related to the ethical implications of these technologies. In emerging markets like Indonesia, the adoption of these frameworks remains limited due to resource constraints, lack of awareness, and resistance to formalizing governance structures. This study explores how Indonesian tech startups integrate digital ethics frameworks into their governance policies and examines the associated benefits and challenges. Through interviews with governance managers and key decision-makers in these startups, the study identifies key trends, including improved transparency and enhanced stakeholder relationships for startups that implement digital ethics practices. However, barriers such as limited expertise, organizational misalignment, and the flexible nature of startups present significant hurdles. The study also highlights the impact of digital ethics on corporate reputation and investor confidence, with startups benefiting from a stronger market presence and increased funding opportunities. In comparison to global practices, Indonesian startups face additional challenges due to cultural attitudes towards corporate responsibility, regulatory gaps, and a slower market readiness for ethical governance reforms. The study provides recommendations for regulatory bodies to create clear guidelines for digital ethics adoption and suggests promoting training for startup leaders to help them integrate these frameworks effectively into their governance policies. These actions can support the long-term sustainability of tech startups, fostering responsible innovation and ethical business practices.